Caliphate Women Limbo and the Action of the European Union - Jiménez-Sánchez, Carolina (Journal of Regional Security, 2022)
Thousands of European women moved to the so-called Caliphate in Syria and Iraq over the past decade. Today, they are in legal limbo, waiting for a response at the Syrian Democratic Forces (SDF) detention camps in various zones. ey took part in Daesh’s functioning, responding to the gender role the organisation gave to them. However, whether they have to be considered terrorists is unclear. Moreover, the counter-terrorist strategies put into practice by states and international organisations are gender-blind. Whether or not they have to be repatriated is controversial, and European countries are giving mixed responses. is article examines three arguments. First, whether the Caliphate women have to be considered terrorist foreign fighters. Second, if the EU is giving or not a gender perspective of counter-terrorist action concerning them. Finally, which would be the implications of the EU Comprehensive Approach for the WPS agenda and its member states? e article suggests that only a truly transformative feminist agenda would eliminate violent extremism in the world.